Bez voiny - Gabrilyan, Alexander (Russia : Ostrov Studio, 2008)
A Red beret is a symbol of the courage and bravery of Russian Army’s Special Forces, a subdivision of the internal security troops of Russia. Only the best of the best make it through training to become Red Berets. Special Forces units spend most of their time in troubled areas of the country. “Without War” follows Russian soldiers on border patrol in Chechnya. But training and life on patrol in Chechnya present very different kinds of challenges. “Without War” is a film about the military and the local people of Chechen villages, about war and peace.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films